Grass-weed challenges, herbicide resistance status and weed control practices across crop establishment systems in Ireland’s mild Atlantic climate - Vijayarajan, Vijaya Bhaskar Alwarnaidu; Fealy, Reamonn M.; Cook, Sarah K.; Onkokesung, Nawaporn; Barth, Susanne; Hennessy, Michael; Forristal, Patrick D. (Frontiers in Agronomy, 2022)
The challenges of grass-weed control in a mild Atlantic climate, added to by the use of non-inversion tillage and limited herbicide options necessitated on-farm knowledge acquisition on grass weeds in Ireland. We surveyed 103 farms from 2020 to 2021 of which, 62 were plough-based and 41 non-inversion tillage. The survey comprised a questionnaire to determine grower demographics, grass-weed challenges, and the adoption of integrated grass-weed control methods (IWM); a grid-square assessment of key grass weeds encountered in one or more cereal fields in both years using weed scores from 0 (absent) to 10 (total weed cover); with samples collected for herbicide-resistance testing. Across the 103 farms, Bromus spp., (62%) and Avena fatua (56%) were the most prevalent but with moderate resistance (8% acetolactate synthase (ALS)-resistant Bromus, 10% acetyl-CoA carboxylase (ACCase)-resistant A. fatua); Lolium multiflorum (13%) and Alopecurus myosuroides (16%) were found on fewer farms but with higher resistance levels (56% ACCase and/or ALS-resistant L. multiflorum, 43% ACCase/ALS-resistant A. myosuroides). Of those who adopted non-inversion tillage, a higher proportion of growers practiced crop rotation (88% cereal/non-cereal break or 83% alternate spring/winter-sown) and used cover crops (71%) than those ploughing (52-66% crop rotation or 19% cover crops), but herbicide use was similar in both systems. Despite higher levels of IWM practices, non-inversion tillage farms had higher weed scores (2.2 ± 0.2 or 3.8 ± 0.7) of B. sterilis and L. multiflorum than ploughing (1.2 ± 0.2 or 2.0 ± 0.7). Considering the complex resistance profile of high resistance-risk species, there is a need for urgent determination of and adoption of effective IWM across systems, specifically, non-inversion tillage. Most of the growers were aware of herbicide-resistant grass weeds (>80%) and most (>90%) used IWM practices (4 or more) to some extent. In our survey, non-inversion tillage farms tended to have younger growers with more formal education and larger farms. This is the first multi-component survey in Ireland establishing long-term monitoring of grass-weed challenges, grower characteristics and IWM practices.